Phenotypic profile and molecular mechanism of resistance in carbapenemase-producing Enterobacterales and Pseudomonas aeruginosa isolates from Brazilian hospitals: implications for the introduction of imipenem-relebactam - Kurtz, Pedro; Del Peloso, Pedro F.; Pribul, Bruno Rocha; Albuquerque, Arthur M.; Antunes, Bianca B. P.; Ramos, Grazielle Vianna; Bozza, Fernando A. (Frontiers in Microbiology, 2025)
Background/ObjectivesCarbapenemase-producing Enterobacterales and P. aeruginosa are critical threats to global public health, especially in high-burden regions such as Brazil. Imipenem-relebactam (IMR), a combination of a carbapenem with a β-lactamase inhibitor, is a promising treatment option against resistant Gram-negative bacteria. This study aimed to characterize phenotypic resistance and molecular mechanisms in clinical isolates from Brazilian hospitals and assess IMR activity.MethodsA prospective multicenter study was conducted across 12 hospitals in Rio de Janeiro. A total of 150 Enterobacterales and 100 P. aeruginosa isolates resistant to carbapenems were collected. Isolates were identified by MALDI-TOF and screened for carbapenemase genes (KPC, NDM, VIM, IMP, OXA-48) using PCR. Susceptibility to IMR was determined by broth microdilution following EUCAST guidelines. Next-generation sequencing (NGS) was performed on a subset of multidrug-resistant isolates.ResultsIMR resistance was identified in 34.5% of K. pneumoniae and 74% of P. aeruginosa isolates. Among Enterobacterales, 21.1% of KPC-producers and 88.9% of OXA-48-producers were resistant to IMR. The bla_KPC gene was predominant, but NDM was increasingly detected. In P. aeruginosa, resistance was largely unrelated to carbapenemase production, implicating porin loss and efflux pumps. NGS revealed extensive co-resistance and multiple virulence genes in K. pneumoniae isolates.ConclusionThis study highlights the emergence of significant resistance to imipenem-relebactam in Brazil, driven by both enzymatic and non-enzymatic mechanisms. Ongoing molecular surveillance and tailored treatment strategies are essential to address the evolving threat of multidrug-resistant Gram-negative infections in endemic regions.